Field notes contributed by Thomas H. Kent, November 28, 1991 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1991)
List of birds and locations contributed by Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed